1988
DOI: 10.2307/1130492
|View full text |Cite
|
Sign up to set email alerts
|

Family Members as Third Parties in Dyadic Family Conflict: Strategies, Alliances, and Outcomes

Abstract: Systems theorists have argued that triads rather than dyads need to be considered as a basic interaction unit, particularly in regard to episodes of conflict. While theoretically appealing, the description of the strategies used and alliances formed when third parties intervene in dyadic conflict presents a number of conceptual and empirical challenges. In the present report, a reliable system for coding such third-party participation in verbal conflicts is described and is used to analyze routine family confl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(115 citation statements)
references
References 0 publications
4
110
0
1
Order By: Relevance
“…These questions were addressed by comparing conflicts when the original combatants were parent-child dyads versus sibling dyads. Although each additional party role has been identified as present in various conflicts (e.g., Ross et al, 1992Ross et al, , 1994, we predicted that alliances would be formed most often compared to the other roles (e.g., judge and additional combatant; Vuchinich et al, 1988). Moreover, we hypothesized that given the children's young ages, standoffs would be the least likely conflict resolution, and disputes would be more likely to end in submissions or compromise (Howe et al, 2002).…”
Section: The Present Studymentioning
confidence: 98%
“…These questions were addressed by comparing conflicts when the original combatants were parent-child dyads versus sibling dyads. Although each additional party role has been identified as present in various conflicts (e.g., Ross et al, 1992Ross et al, , 1994, we predicted that alliances would be formed most often compared to the other roles (e.g., judge and additional combatant; Vuchinich et al, 1988). Moreover, we hypothesized that given the children's young ages, standoffs would be the least likely conflict resolution, and disputes would be more likely to end in submissions or compromise (Howe et al, 2002).…”
Section: The Present Studymentioning
confidence: 98%
“…For example, Cummings and Davies (2011) found that child-focused, angry, and verbally or physically aggressive conflict is particularly harmful. However, family systems (Emery, Fincham, & Cummings, 1992) and emotional security (Cummings & Davies, 2011) theory, clinical observations (Emery, 2011;Maldonado, 2014), and research on children caught in the middle (Buchanan, Maccoby, & Dornbusch, 1991;Buehler et al, 1997;Vuchinich, Emery, & Cassidy, 1988) all suggest that children do not have to directly observe parental disputes to be harmed by them. Denigration may be one form of harmful conflict in which children do not directly observe a dispute.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a few studies have coded taped family interactions (Vuchinich et al 1988;Wood et al 1989). Most of the triangle research has studied the effects of triangling on the development and functioning of children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…One study (Belsky and Isabella 1985) examined the intergenerational effects of the primary triangle relationships on new parents' attachment styles with their children. Vuchinich et al (1988) demonstrated how third parties influence dyadic conflict in family interaction.…”
Section: Introductionmentioning
confidence: 99%